Question & Answer
QUESTION

Determine the value of y:
$15\left( {y - 4} \right) - 2\left( {y - 9} \right) + 5\left( {y + 6} \right) = 0$
$
  {\text{A}}{\text{. y = }}\dfrac{1}{7} \\
  {\text{B}}{\text{. y = }}\dfrac{3}{5} \\
  {\text{C}}{\text{. y = }}\dfrac{5}{2} \\
  {\text{D}}{\text{. y = }}\dfrac{2}{3} \\
 $

ANSWER Verified Verified
Hint: To solve this question first we have to expand the equation completely and then do a simplification.

Complete step-by-step answer:

We have

$15\left( {y - 4} \right) - 2\left( {y - 9} \right) + 5\left( {y + 6} \right) = 0$

On expanding that means on multiplying inside the bracket we get,

$

   \Rightarrow 15y - 60 - 2y + 18 + 5y + 30 = 0 \\

   \Rightarrow 18y - 12 = 0 \\

   \Rightarrow y = \dfrac{{12}}{{18}} = \dfrac{2}{3} \\

    \\

 $

Hence option D is the correct option.

Note: Whenever we get this type of question the key concept of solving it is we have to go straight forward that means just do simple calculation and get an answer and there is nothing in this type of question.